ON THE UNIVALENCE OF A NEW INTEGRAL PERATOR - Amer, Aisha (مجلة كلية التربية العلمية, 2017)
Motivated by the linear operator studied by the author in [2, 3], the author introduce and study a new general integral operator defined on the class of normalized analytic function in the unit disc. This operator is motivated by many researchers. With this operator univalence conditions for the normalized analytic function in the open unit disc are obtained. Indeed, the author present a few conditions of univalency for our integral operator. . Having the integral operator, there are interesting properties of normalized function in the unit disc for univalent conditions for an integral operator. In addition, the author also find some interesting corollaries on the class of normalized analytic of functions in the open unit disc.